2021
DOI: 10.1093/neuros/nyab240
|View full text |Cite
|
Sign up to set email alerts
|

Poor Fusion Rates Following Cervical Corpectomy Reconstructed With an Expandable Cage: Minimum 2-Year Radiographic and Clinical Outcomes

Abstract: BACKGROUND Expandable cages are often used to reconstruct cervical corpectomies but there are few long-term follow-up studies with large numbers. OBJECTIVE To analyze the clinical and radiographic results of cervical corpectomy reconstructed with expandable cages for degenerative stenosis. METHODS We performed a retrospective analysis of 78 patients with dege… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 25 publications
2
7
0
Order By: Relevance
“…In our study, fusion rate in both study group was 85% (expandable cage alone—78.33% and with anterior cervical plate—95%), which is almost similar to the study done by Pojskic et al, Brenke et al, Art et al, Hassan Allouch et al, Cappelletto et al, Byvaltsev et al, and Tohamy et al 13 14 15 16 17 18 19 The placement of expandable cage is very smooth and avoids any major damage to the vertebral endplates. It is an instinctive thought that subsidence should be lower in the cervical spine because of less axial loading in contrast to the dorsal and lumbar spine.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…In our study, fusion rate in both study group was 85% (expandable cage alone—78.33% and with anterior cervical plate—95%), which is almost similar to the study done by Pojskic et al, Brenke et al, Art et al, Hassan Allouch et al, Cappelletto et al, Byvaltsev et al, and Tohamy et al 13 14 15 16 17 18 19 The placement of expandable cage is very smooth and avoids any major damage to the vertebral endplates. It is an instinctive thought that subsidence should be lower in the cervical spine because of less axial loading in contrast to the dorsal and lumbar spine.…”
Section: Discussionsupporting
confidence: 89%
“…One of the subsidence prevention features of expandable cage is limited footprint surface area which leads to less fusion due to inadequate graft-host bone contact and in turn increases the risk of implant failure as compare with other nonexpendable cage so anterior cervical plating is useful 21. Cage subsidence in our study was 15% (expandable cage alone-21.67% and with anterior cervical plate-5%), similar findings were also reported by Brenke et al (14%) and Tohamy et al (5.68-14.71%), while in a study done by Pojskic et al and Art et al cage subsidence was relatively higher (24.4% and 42.7%, respectively) [13][14][15][16][17][18][19]. Previous studies have reported that expandable cages allow for improvement in cervical lordosis but no large comparative studies done evaluating the effect on cervical lordosis 3.…”
supporting
confidence: 89%
See 1 more Smart Citation
“…However, these approaches are more invasive and often associated with complications. For example, unilateral facet removal tends to cause postoperative instability 10 , and corpectomy in anterior approaches requires xation with cages and plates 14,15 . Also, their approach routes are often not familiar to ordinary spine surgeons.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, screw pull-out or breakage may occur due to the change of the force applied to the screw, which accelerates the deterioration of the plate system instability and causes an instrument failure or telescoping in which the entire surgical segment is collapsed [10,28]. In rare cases of catastrophic instrument failure may require reoperation in long-term non-union [29,30].…”
Section: Discussionmentioning
confidence: 99%